Habeas Data, Habemus Algorithms: Algorithmic Intervention in Public Interest Decision-Making in Colombia - Chenou, Jean-Marie; Rodríguez Valenzuela, Laura Estefanía (Law, State and Telecommunications Review, 2021)
[Purpose] Automated decision-making and algorithmic governance are increasingly implemented in Latin America in order to improve efficiency in public institutions. However, regulatory frameworks are limited, and the uncritical adoption of technological solutions might undermine fundamental rights, especially of marginalized and vulnerable groups. [Methodology] The article explores two cases of automated decision-making in the Colombian public sector from a social justice perspective. It also outlines current debates on the regulation of artificial intelligence and algorithmic governance at the global level. [Findings] The article shows that the techno-optimistic discourse on the improvement of decision-making through the adoption of algorithms and artificial intelligence ignores the implications in terms of fundamental rights. This leads to the adoption of technologies without the necessary transparency and policy debates. [Practical Implications] The outline of current debates in other regions could inform policy debates in Colombia and Latin America. They provide some guidelines on how to prevent some of the most serious pitfalls of automated decision-making in the public sector. [Originality] While most of the debates on automated decision-making focus on the Global North, this article explores two cases from Colombia and discusses the necessary policy debates on algorithmic governance in Latin America.